Utilizing TPACK to Mitigate Learning Loss in Junior High Schools: An Empirical Study from Riau Province, Indonesia - Fadly Azhar; Indra Primahardani; M. Yogi Riyantama Isjoni; Dedi Futra; Apen Sintia (AL-ISHLAH: Jurnal Pendidikan, 2025)
The COVID-19 pandemic has caused significant learning loss among Indonesian students, particularly at the junior secondary level. This disruption highlights the urgent need for effective strategies to restore educational quality. The Technological Pedagogical Content Knowledge (TPACK) framework offers a promising approach for integrating technology into teaching to mitigate such losses. This study involved 719 junior high school teachers from Riau Province, selected through stratified random sampling. Data were collected using a validated questionnaire measuring teachers’ TPACK competence, technology utilization, and efforts to mitigate learning loss. Descriptive and inferential statistical analyses were conducted using SPSS, including path and correlation analyses. The findings reveal that both the construction and utilization of TPACK-based ICT significantly contributed to reducing learning loss, with a combined influence of 88.7%. Teachers with strong TPACK competencies demonstrated greater effectiveness in implementing technology-enhanced learning. However, challenges such as low digital literacy and unequal access to infrastructure remain significant barriers. These results underscore the strategic role of teacher competence and infrastructure readiness in addressing post-pandemic learning gaps. The strong correlation between TPACK use and learning loss mitigation suggests that targeted professional development and digital transformation policies are essential. Improving TPACK competence among educators and enhancing digital infrastructure are critical to mitigating learning loss. The study advocates for national policies that institutionalize TPACK-based training and equitable technology access to promote pedagogical innovation and reduce educational disparities.